Interest Management As A Driver Of Success In Learning Al-Qur'an Memory At Al-Amanah Islamic School - Arfa Marettiani Yusmiawati; Rina Eka Widjayanti (Journal of Innovation, Business Management and Entrepreneurship, 2025)
Interest is an internal factor that significantly influences learning success, especially in the memorization of the Qur'an (tahfidz) which requires consistency, motivation, and high discipline. This study aims to examine how the management of students' interest can serve as a driving force for the success of tahfidz learning at Al-Amanah Islamic School. This research employs a qualitative approach using a case study method. The results show that well-planned and consistent interest management strategies through personal approaches, varied learning methods, and supportive educational environments are effective in increasing students' enthusiasm and achievement in memorizing the Qur'an.